2015
DOI: 10.1021/acs.orglett.5b01466
|View full text |Cite
|
Sign up to set email alerts
|

Privilege Ynone Synthesis via Palladium-Catalyzed Alkynylation of “Super-Active Esters”

Abstract: A neat palladium-catalyzed alkynylation reaction was developed with "super-active ester" as the carbonyl electrophile, which provides a clean and efficient synthetic protocol for a broad array of ynone compounds under CO-, Cu-, ligand-, and base-free conditions. The superior activity of triazine ester was rationalized by the strong electron-withdrawing ability and the unique affinity of triazine on palladium. A mechanistic experiment clearly demonstrated that the N-Pd coordination of triazine plays a crucial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…The experimental data unveiled the complicated electronic factor that governed the activity of alkynone, and further confirmed that the alkynone with methoxy group (L2) is the best for the palladium catalyst system. Through reasonable screening of the amount of alkynone ligands, it was found that the reaction yield increased first and then decreased when increasing the amount of ligand (Table 1) To understand the electronic factors of the acceleration capabilities of α, β-alkynone, nine parasubstituted aromatic allkynones were prepared according to the method outlined in the literature [19] and evaluated in this reaction. The alkynone ligand L 1 gave a yield of 42%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental data unveiled the complicated electronic factor that governed the activity of alkynone, and further confirmed that the alkynone with methoxy group (L2) is the best for the palladium catalyst system. Through reasonable screening of the amount of alkynone ligands, it was found that the reaction yield increased first and then decreased when increasing the amount of ligand (Table 1) To understand the electronic factors of the acceleration capabilities of α, β-alkynone, nine parasubstituted aromatic allkynones were prepared according to the method outlined in the literature [19] and evaluated in this reaction. The alkynone ligand L 1 gave a yield of 42%.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction mixture was stirred at 50 • C for 10 h. After the reaction was completed, the reaction mixture was concentrated under a vacuum. The crude product was purified by column chromatography on silica gel to afford the corresponding product [19] (see Supplementary Materials).…”
Section: Synthesis and Spectroscopic Data Of α β-Alkynone Ligandsmentioning
confidence: 99%
“…However, as far as our knowledge, few reports have been focused on the one‐pot synthesis of indoles directly from anilines and α,β ‐ynones. Moreover, our group has developed a convenient approach for the production of α,β ‐ynones, recently . Therefore, we wish to report our novel strategy for the synthesis of indoles directly from anilines and α,β ‐ynones via the cascade procedure of aza ‐Michael addition and C−H functionalization in one pot (Scheme , Path C).…”
Section: Methodsmentioning
confidence: 99%
“…Tolman and co‐workers recognized palladium catalyzed ester decarbonylation to yield alkene, which can undergo tandem Heck coupling reaction with other activated ester to afford stilbenes (Scheme 1a) . Similarly, Gao and co‐workers demonstrated convenient synthesis of ynones via palladium catalyzed alkynylation of super active esters (Scheme b) . In related work, Zeng and co‐workers reported one pot synthesis of aryl ketone derivatives from aromatic acids via activated ester using palladium catalyzed Suzuki coupling reaction (Scheme c) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hu and co‐workers explored cross‐coupling of alkyl redox‐active esters with amines and imines using photoredox and copper catalysts . Additionally, esters proved to be an excellent acylating agent by reacting with aryl boronic acid [13],[20] and aryl/alkyl terminal alkynes . Unfortunately, the existing methodologies suffer from certain drawbacks such as the requirement for transition metal catalysts (Ru, Ni and Pd), harsh reaction conditions, longer reaction time and excessive additives.…”
Section: Introductionmentioning
confidence: 99%